The translator is a traitor: The case of the English standard version - O'Collins, Gerald (The Australasian Catholic record, 2022)
This article examines the worth of the English Standard Version (ESV), a translation of the Bible that privileges word for word rather than meaning for meaning. Inaccuracies are often caused by refusing to use inclusive language. At times, the ESV introduces unnecessary and even misleading variations. Even worse are interpolations that add English words to which nothing corresponds in the original Greek. After the discovery of the Dead Sea Scrolls, it is a fatal flaw to suppose that translators of the Old testament can almost always follow the much later Masoretic text.